The Influence Of Capital Structure And Company Size On Financial Performance On The Construction And Building Sub Sector Listed On IDX 2016-2020 - nurdina nurdina; R.Yudi Sidharta; Arika Fatmawati Ningrum (Universitas Islam Lamongan, 2023)
the company's abilities to make profits using the exclusive period can b measured by the success and abilities of the company to use its assets productively. For profits to b achieved, companies need components that can increase their profitability. This research uses a quantitative approach method. The analysis was taken according to secondary data from the annuals report of construction & building sub-sector companies listed on the IDX in 2016-2020. The population is 24 construction & building companies listed on the IDX. The samples technique used purposive sampling, using the criteria the company carried out in the study there were still 8 samples of companies or 40 samples of observations. the results of this study reveal that the structure capital & sizes on financial performance.